PRENATAL GROWTH AND BREEDING STATUS OF Cynopteris brachyotis - RAHMAT, LIBAR (UNIVERSITI MALAYSIA SARAWAK(UNIMAS), 2014)
Cynopterus brachyotis is one of seven species under genus Cynopterus (Megachiroptera, Pteropodidae). I studied the prenatal growth and development of this species. I measured the forearm length (FAL), crown rump length (CRL) and greatest length of skull (GLS). Linear regression for general growth trajectories were generated by plotting FAL and CRL against GLS. Both FAL and CRL showed positive relationship with GLS. The embryos of C. brachyotis have been successfully staged by referring to recent bat staging system and the expected mating and birthing month were estimated. I estimate the following regarding C.brachyotis reproduction. In general, the reproduction of C.brachyotis can be characterized as aseasonally polyoestrus. The peak birth season in C.brachyotis does not correspond to the season of greater rainfall (Nov-Jan) and fruiting season (March-June). This provides indication on how this species is abundance and successful.